2011
DOI: 10.3174/ajnr.a2597
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Geometry Change Because of Endovascular Stent Placement for Anterior Communicating Artery Aneurysms

Abstract: BACKGROUND AND PURPOSE:Hemodynamics have been shown to play an important role in the initiation and progress of intracranial aneurysms, and are considered well-related to vascular configuration. The purpose of this study was to quantify the vascular geometry change due to intracranial stent placement and to discuss its potential effects on hemodynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 19 publications
1
44
0
1
Order By: Relevance
“…Intracranial stents have a multifactorial favorable role in aneurysm embolization: It may enable dense coil mass packing [16,17], change vascular morphology, induce intraaneurysmal flow modifications [18][19][20][21][22], and provide a structural basis for endothelialization [23,24]. However, the use of stent-assisted coil embolization more commonly has been reserved for unruptured aneurysms in order to determine the difference between thromboembolic events and hemorrhagic events when treating acutely ruptured aneurysms compared with unruptured ones.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial stents have a multifactorial favorable role in aneurysm embolization: It may enable dense coil mass packing [16,17], change vascular morphology, induce intraaneurysmal flow modifications [18][19][20][21][22], and provide a structural basis for endothelialization [23,24]. However, the use of stent-assisted coil embolization more commonly has been reserved for unruptured aneurysms in order to determine the difference between thromboembolic events and hemorrhagic events when treating acutely ruptured aneurysms compared with unruptured ones.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, no cases of in-stent occlusion were mentioned in the previous studies. 3,5) The 3D analysis of the vessel revealed that the change in vascular geometry caused the kinking and occlusion of the vessel. Delayed in-stent occlusion rarely occurs after the treatment of cerebral aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…Stent-related changes in vascular geometry have been observed in the treatment of cerebral aneurysms. 3,5) Vascular geometry was changed by stent placement in anterior communicating artery aneurysms, and the angle of change ranged from 7.609to 74.889 , with a mean of 29.959 . 5) Change in vascular geometry also occurred after stent placement for bifurcation aneurysms, and the vascular angles changed by a mean of 189on immediate angiograms and 349on follow-up angiograms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, although a recent study suggested that placement of intracranial stent changed the parent vascular configuration and indirectly affected the local hemodynamics, our CFD analysis could not take this vascular configuration into consideration. 3) Third, the assumption of the flow conditions, fluid properties, inlet velocity, and outlet flow splits for the CFD simulations were made to reflect typical conditions in the cerebral circulation but may not be applicable to all possible clinical situations. Last, although our data emphasize the role of the hemodynamic effects of intracranial stents, the biological potential of intracranial stents might also accelerate endothelialization, intimal coverage, and subsequent occlusion of incompletely embolized cerebral aneurysms.…”
Section: Discussionmentioning
confidence: 99%